2023
DOI: 10.1112/jlms.12800
|View full text |Cite
|
Sign up to set email alerts
|

From zero surgeries to candidates for exotic definite 4‐manifolds

Abstract: One strategy for distinguishing smooth structures on closed 4‐manifolds is to produce a knot in that is slice in one smooth filling of but not slice in some homeomorphic smooth filling . In this paper, we explore how 0‐surgery homeomorphisms can be used to potentially construct exotic pairs of this form. To systematically generate a plethora of candidates for exotic pairs, we give a fully general construction of pairs of knots with the same zero surgeries. By computer experimentation, we find five topologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
(178 reference statements)
1
4
0
Order By: Relevance
“…The author would also like to thank his advisors Bob Gompf and John Luecke for their help and support. As noted in [17], some cases of the above results were already established by others. Dunfield and Gong showed that 𝐾 6 , … , 𝐾 21 are not slice using their program to compute twisted Alexander polynomial [4] and Kyle Hayden showed that 𝑍 1 is standard.…”
Section: A C K N O W L E D G M E N T Ssupporting
confidence: 76%
See 4 more Smart Citations
“…The author would also like to thank his advisors Bob Gompf and John Luecke for their help and support. As noted in [17], some cases of the above results were already established by others. Dunfield and Gong showed that 𝐾 6 , … , 𝐾 21 are not slice using their program to compute twisted Alexander polynomial [4] and Kyle Hayden showed that 𝑍 1 is standard.…”
Section: A C K N O W L E D G M E N T Ssupporting
confidence: 76%
“…The classical trace embedding lemma asserts a knot 𝐾 is slice if and only if the zero trace 𝑋 0 (𝐾) smoothly embeds in 𝑆 4 . We have an analogous statement for a knot to be 𝐻-slice in 𝑋. Lemma 2.2 (H-slice trace embedding lemma, [17,Lemma 3.5]). A knot 𝐾 is 𝐻-slice in 𝑋 if and only if −𝑋 0 (𝐾) smoothly embeds in 𝑋 by an embedding that induces the zero map on second homology.…”
Section: H-slice Knots and Zero Surgery Homeomorphismsmentioning
confidence: 96%
See 3 more Smart Citations